Avaliação multicritério das alternativas energéticas do Brasil para produção de hidrogênio por eletrólise alcalina da água para o setor automotivo - Francisco Edvan Bezerra Feitosa (2019)
This work puts into discussion in the academic sphere, some important points and proposes four new ways of thinking, for the energy and automotive transport sectors of Brazil. First point: decision-making regarding energy takes into account only the economic and financial aspects, which benefit only business and investors in the sector. In the new way of thinking, decisions regarding energy will be made considering multi-criteria analysis, which also include aspects related to the sustainability of the planet, benefiting business, investors, the environment and society Brazilian. Second point: The Brazilian energy matrix is composed of 56.5% of non-renewable sources. In the new way of thinking, vehicles that consume petroleum products can be gradually replaced by hydrogen-powered vehicles produced from the electrolysis of water, making use of electricity generated by renewable source, replacing the fossil fuels. Third point: The Brazilian automotive sector uses engines, based on Otto thermodynamic cycle as a theoretical principle, which are recognized as low efficiency. In the new way of thinking, these vehicles can be gradually replaced by electric motor-powered vehicles with electric power supplied by fuel cells, which are admittedly more efficient, totally free of gas emissions greenhouse and polluting gases. Fourth point: In Brazil, the fuels used in the automotive sector are petroleum derivatives, which cause harmful effects on the environment and the health of people. In the new way of thinking, three energetic sources - the sun, wind and water of rivers - can be used to produce electricity for a possible hydrogen program for the automotive sector. In addition, it was concluded that it is possible to produce hydrogen on a large scale from alkaline electrolysis of water; that countries such as Japan, the United States of America and some of the European Union have already tested hydrogen production technologies and fuel cell-powered vehicles, and that they are viable. In this work, two evaluations were carried out using the multicriteria method of supporting MACBETH decision making, considering economic, financial, technological, environmental and social criteria. Among the main conclusions of the analyses carried out, it was found that photovoltaic solar energy is an attractive alternative for the production of electricity for a possible automotive hydrogen production program and that "Hydrogen" is more attractive than that conventional fuels used in Brazil. Finally, this work is justified by supporting the sustainability of the Planet, since hydrogen is a clean, high-density energy fuel, which can contribute to solving internal energy and environmental problems, and contributing to the reduction of global warming.